PERENCANAAN TEBAL PERKERASAN BETON SEMEN DAN RENCANA ANGGARAN BIAYA PADA RUAS JALAN LOA SUMBER LEMPATAN KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - NO, AYET (KURVA S JURNAL MAHASISWA, 2014)
Proeses Pavement road is one element of highway construction is very important in order to smooth ground transportation so as to provide comfort and safety for its users, so it needs to be well planned based on ISO standards and planning criteria PdT-14-2003 prevailing in Indonesia.Location Roads Source Lempatan District of Loa Kulu Regency, is a road that is necessary to improve the pavement running, because technically the condition of these roads in poor condition with moderate to severe, thereby reducing comfort and smooth flow of public road users also economic development Subdistrict Loa Kulu.Type of road pavement, can be Flexible Pavement (flexible pavement), Cement Concrete Pavement (rigid pavement) and Pavement Composite, which combines the cement concrete and flexible pavements. Especially for Perkeraaan Kaku / Concrete Cement (rigid pavement) made of either concrete or cement concrete without reinforcement and more widely used on roads that have a high volume of64heavy vehicles and frequent flooding Rigid Pavement work execution / Concrete Cement (Rigid Pavement)must be considered carefully the quality of the concrete will be required in accordance with the calculation of the K-350 (350 kg / cm2), and the age of the concrete period of 28 days in the process pembetonannya so no damage.In theexecution of the work, if the market does not exist diameter iron according to the results of planning, it can be used with iron diamteter approaching the re-calculation provisions should be made pembesian the same pavement thickness of 30 cm.In connection with the above description, the authors conducted a study onthe above mentioned roads by taking the title: "Cement Concrete Pavement Thickness Planning and Budget Plan On Roads Source Lempatan Loa Kulu District of Kutai regency"The contents of this final project is As mentioned above, it can be made of research, is as follows What is thick cement concrete pavement during the design life of 20 years with two first Metude menggukan Metude SNI PdT-14-2003 and second calculation Budget Plan based Engineering Estimate (EE).How much of the work of the cement concrete pavement accordance with the title essay, about the calculation of the cost of cement concrete pavement work (rigid pavement) on these roads, using methods SNI PdT-14-2003 and Calculation Budget Plan based Engineering Estimate (EE) , Rigid Pavement work execution / Concrete Cement (Rigid Pavement) to be aware of the quality of concrete as required in accordance with the calculation of the K-350 (350 kg / cm2), and the age of the concrete period of 28 days in the process pembetonannya so no damage.